Macroeconomic effects of rental housing regulations: The case of Germany in 1950-2015 - Konstantin A. Cholodilin; Julien Licheron (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Despite rather skeptical attitude of the economists toward the state intervention in the housing markets, the policy makers and general public typically are supporting it. As a result, in many European countries, since World War I the rent and eviction controls as well as social housing policies remain an important element of the government economic policies. Nevertheless, the macroeconomic effects of such regulations are largely unknown. In this paper, we evaluate the effects of government rental market regulations on real house prices, price-to-rent, and price- to-income ratios, real rents, and new housing construction in Germany in 1950 to 2015. The regulations are measured by the indices developed by the authors based on a thorough analysis of the legal acts issued mostly by the central government but also by the regional authorities between 1914 and 2015.
Keywords: C22; O18; R38; 330; housing market; government regulations; Germany; housing prices and rents; new residential construction